Detection of Ehrlichia canis by polymerase chain reaction from Portugal. - Alexandre, Nuno; Sofia Santos, Ana; Núncio, Maria Sofia; de Sousa, Rita; Boinas, Fernando; Bacellar, Fátima (Elsevier, 2009)
Antibodies against Ehrlichia canis, the cause of canine monocytic ehrlichiosis, have been reported previously in clinically ill and stray dogs from Portugal. In this study, the 16S rRNA gene of E. canis was detected by the polymerase chain reaction (PCR) in 12/55 (22%) of dogs with suspected tick-borne disease in the Algarve region in Portugal.
Keywords: Ehrlichia canis; Polymerase chain reaction; Canine; Portugal